PENGARUH KEBISINGAN DAN IKLIM KERJA TERHADAP STRES KERJA DI PABRIK PRODUKSI MAKANAN HEWAN - Wiediartini; Denny Dermawan (Journal of Research and Technology, 2019)
Noise and heat have become a problem for a worker in the animal food processing company. The aim of this study was to analyze the influence of noise and heat to stress. The result showed a relationship between noise, heat, and stress (sig 0,003<0,05). A moderate correlation between noise, heat, and stress was also observed (r=0,561). No differences between the two groups of age, gender, and status were found with t-test. Reducing noise and heat were necessary to be executed through engineering and administrative control. There was no need to differ the treatment to control the stress between a group of gender, age, and status.